Hidden in Plain Sight: Incidental Diagnosis of Metastatic Papillary Thyroid Microcarcinoma Without Radiologically Apparent Thyroid Tumor - Natalie Rivera Vargas, MD; Moises Matos, MD; Mustafa Kinaan, MD, FACE (AACE Clinical Case Reports)
Background/Objective: Papillary thyroid cancer (PTC) is considered the most common form of thyroid cancer. Papillary thyroid microcarcinomas (PTMCs) are defined as papillary carcinomas that are <1 cm and are often identified on surgical pathology but may be missed by ultrasound imaging. Case Report: Our case describes a 24-year-old woman who initially presented with a right lateral neck lump. This was thought to be a lipoma, and no workup was performed until it began to grow during pregnancy 3 to 4 years after initial presentation. The patient underwent excision with findings of a level 5B lymph node with pathology consistent with PTC, follicular variant. Neck ultrasound performed in an imaging center and in our clinic did not reveal thyroid nodules or abnormal appearing lymph nodes. Solid tumor profiling assay identified a neurotrophic tropomyosin receptor kinase (NTRK)-3 fusion: ETV6(4)-NTRK3(14) mutation. Discussion: PTMCs are identified with increased frequency due to improved ultrasound imaging and fine needle aspiration techniques. PTMCs are often associated with a benign course and are rarely metastatic. There has been growing interest in NTRK fusion mutations in PTC that has been associated with an increased risk of metastasis. Conclusion: This case is unusual in that multiple cervical nodal metastases were present even without a sizable primary thyroid tumor. Although more studies are needed to elucidate the clinical and prognostic significance of NTRK fusion mutations in PTMC, their response to tropomyosin receptor kinase inhibitors may represent a future pathway for treatment.